Answer:
A. 111.65
Step-by-step explanation:
This scenario can be interpreted like a triangle ABC where A and B are islands and C is the point from where the captain is 160 miles from island B.
a = 160
b = 260
c = 250
Law of cosines
[tex]c^2 = a^2 + b^2 - 2(ab)Cos(C)\\Arranging\ as\\2ab \ cos\ C = a^2+b^2-c^2\\2(160)(260)\ cos\ C = (160)^2+(260)^2- (250)^2\\83200\ cos\ C=25600+67600-62500\\83200\ cos\ C=30700\\cos\ C= \frac{30700}{83200}\\cos\ C=0.36899\\C = arccos\ (0.36899)\\C = 68.35[/tex]
The internal angle is 68.35°
We have to find the external angle to find the bearing the captain should turn
Using the rule of supplimentary angles:
The external angle = 180 - 68.35 = 111.65°
Therefore, the captain should turn 111.65° so that he would be heading straight towards island B.
Hence, option 1 is correct ..
Answer: Option 'a' is correct.
Step-by-step explanation:
Since we have given that
AB = 250 feet
AC = 260 feet
BC = 160 feet
We need to find the angle C that is heading straight towards island B.
We will apply "Law of cosine":
[tex]\cos C=\dfrac{a^2+b^2-c^2}{2ab}\\\\\cos C=\dfrac{160^2+260^2-250^2}{2\times 160\times 260}\\\\\cos C=0.368\\\\C=\cos^{-1}(0.368)\\\\C=68.40^\circ[/tex]
Exterior angle would be
[tex]180-68.40=111.65^\circ[/tex]
Hence, Option 'a' is correct.
Amanda owns a clothing store that sells graphic t-shirts. n is the number of shirts she sells each month. the revenue function of her store is r = 15n. the cost function of her store is c = 9n + 450. using your calculator, what is the break-even point of amanda's store?
Answer:
The break- even point is attained when n=75
Step-by-step explanation:
The break-even point is defined as the point where revenue is equal to cost.
We take the equation for revenue r=15n, and set it equal to the equation c=9n+450
15n=9n+450
Subtract 9n from both sides:
6n=450
Divide both sides by 6.
6n/6=450/6
n=75
The break- even point is attained when n=75....
Final answer:
To determine Amanda's store's break-even point, set the revenue equal to the cost function and solve for n to find 75 shirts.
Explanation:
To find the break-even point of Amanda's store:
Set the revenue function equal to the cost function: 15n = 9n + 450
Solve for n: n = 75
Therefore, the break-even point is when Amanda sells 75 graphic t-shirts.
the sum of four consecutive odd integers is -72. What is the value of the four intergers
Answer:
let the integers be x, x+2, x+4 and x+6
therefore,
x + x+2 + x+4 + x+6 = -72
=> 4x + 12 = -72
=> 4x = -72 - 12
=> x = -84/4
=> x = -21
therefore the integers are: -21, -19, -17, -15
[tex]\huge\boxed{\text{-21, -19, -17, -15}}[/tex]
Represent this mathematically. [tex]x+(x+2)+(x+4)+(x+6)=-72[/tex]
Combine like terms. [tex]4x+12=-72[/tex]
Subtract 12 from both sides. [tex]4x=-84[/tex]
Divide both sides by 4. [tex]x=-21[/tex]
Find the numbers by adding 2 each time. [tex]-21, -19, -17, -15[/tex]
What was done to the quadratic parent function F(x) = x2 to get the
function G(x) = x2 - 3? 0)
A.Shifted 3 units to the right
B. Vertically stretched by multiplying by 3
C.Shifted 3 units down
D.Shifted 3 units to the left
ОА ОВ Oc OD
HINT
SUBMIT
Answer:
Option C.
Step-by-step explanation:
If k<0, the function g(x) = f(x) + k represents the function f(x) shifted k units downwards.
In this case, given that k=-3 (k<0). The graph was shifted 3 units down. Therefore, the correct option is Option C.
1. If x[tex]y^{2}[/tex] and xy are perfect squares, where x and y are positive integers, what is the smallest value of x + y?
Answer:
8
Step-by-step explanation:
xy^2 = k*k y^2 x = k * k so x has to be a perfect square.
xy is a perfect square which means that since x is a perfect square (see above) then y will have to be as well
There is nothing that prohibits x = 4 and y = 4 as being the answer where x = y.
I think the smallest possible value for x + y is 8.
This excludes any possibility of 1 or 0 in some combination, although I would look into 1.
a^-3 over a^-2b^-5 write without rational notation and move all terms to numerator
Answer:
[tex]\large\boxed{\dfrac{a^{-3}}{a^{-2}b^{-5}}=a^{-1}b^5}[/tex]
Step-by-step explanation:
[tex]\dfrac{a^{-3}}{a^{-2}b^{-5}}=a^{-3}\cdot\dfrac{1}{a^{-2}}\cdot\dfrac{1}{b^{-5}}\qquad\text{use}\ x^{-n}=\dfrac{1}{x^n}\\\\=a^{-3}\cdot a^2\cdot b^5\qquad\text{use}\ x^n\cdot x^m=x^{n+m}\\\\=a^{-3+2}b^5=a^{-1}b^5[/tex]
Find the value of y.
Answer:
=6√3 the third option.
Step-by-step explanation:
We can use the Pythagoras theorem to find the value of y. We need two equations that include y.
a²+b²=c²
c=9+3=12
x²+y²=12²
x²=144 - y².........i (This is the first equation)
We can also express it in another way but let us find the perpendicular dropped to c.
perpendicular²= x²-3²=x²-9 according to the Pythagoras theorem.
y²=(x²-9)+9²
y²=x²+72
x²=y²-72....ii( this is the second equation
Let us equate the two.
y²-72=144-y²
2y²=144+72
2y²=216
y²=108
y=√108
In Surd form √108=√(36×3)=6√3
y=6√3
In the Pythagorean Theorem, what
does the "a" stand for?
a2 + b2 = c2
A. The longest side, or hypotenuse, of a right triangle.
B. One of the sides, or legs, that make up the right
angle.
C. Any unknown side of a right triangle.
Answer:
B. One of the sides, or legs, that make up the right angle.
Step-by-step explanation:
The Pythagoras Theorem applies to the right-angled triangles. It is basically a relationship between the sizes of the all lengths of the triangle. The Pythagoras Theorem is given by:
C^2 = A^2 + B^2; where A and B are perpendicular and base respectively, and C is the hypotenuse. It is interesting to note that A can either be the perpendicular or the base of the right angled triangle. Same goes for B; it can be either the perpendicular or the base. Both the perpendicular and the base intersect at 90 degrees. But both cannot be the hypotenuse. Therefore, the variable A in the Pythagoras Theorem is one of the sides, or legs, that make up the right angle, i.e. Option B is the correct answer!!!
The average car sold from Dealership A is $25,700. If the sales person receives 1.5% commission on the price of the car, how much commission is made on average per car sold?
Answer:
385.5 USD
Step-by-step explanation:
If an average car is sold for 25,700 USD, and the sales person gets 1.5% commission of it, we can easily get to the amount of money that the sales person managed to get from each sale.
The 25,700 should be divided by 100, as that is number of total percentage:
25,700 / 100 = 257
So we have 1% being 257 USD, but we need 1.5%, so we should multiple the 257 USD by 1.5%:
257 x 1.5 = 385.5
So we get a result of 385.5 USD, which is the amount the sales person makes from commissions on average per sold car.
10x^3 y^-5 z^-2 if x=3 y=2 and z=5 express your answer as a reduced fraction
Answer:
[tex]\large\boxed{\dfrac{27}{80}}[/tex]
Step-by-step explanation:
Put x = 3, y = 2 and z = 5 to the given expression [tex]10x^3y^{-5}z^{-2}[/tex]:
[tex]10(3^3)(2^{-5})(5^{-2})\qquad\text{use}\ a^{-n}=\dfrac{1}{a^n}\\\\=\dfrac{10(27)}{(2^5)(5^2)}=\dfrac{270}{(32)(25)}=\dfrac{270}{800}=\dfrac{27}{80}[/tex]
Write the slope-intercept form of the equation that passes through the point (2, 3) and is perpendicular to the line y = 5/8x - 4
Answer:
[tex]\large\boxed{y=-\dfrac{8}{5}x+\dfrac{31}{5}}[/tex]
Step-by-step explanation:
[tex]\text{The slope-intercept form of an equation of a line:}\\\\y=mx+b\\\\m-slope\\b-y-intercept[/tex]
[tex]\text{Let}\\\\k:y=m_1x+b_1\\\\l:y=m_2x+b_2\\\\l\ \perp\ k\iff m_1m_2=-1\to m_2=-\dfrac{1}{m_1}\\\\l\ \parallel\ k\iff m_1=m_2\\\\--------------------------[/tex]
[tex]\text{We have:}\\\\y=\dfrac{5}{8}x-4\to m_1=\dfrac{5}{8}\\\\\text{The slope of a perpendicular line:}\ m_2=-\dfrac{1}{\frac{5}{8}}=-\dfrac{8}{5}\\\\\text{The equation:}\\\\y=-\dfrac{8}{5}x+b\\\\\text{Put the coordinates of the point (2, 3) to the equation:}\\\\3=-\dfrac{8}{5}(2)+b\qquad\text{solve for}\ b\\\\3=-\dfrac{16}{5}+b\qquad\text{add}\ \dfrac{16}{5}\ \text{to both sides}\\\\\dfrac{15}{5}+\dfrac{16}{5}=b\to b=\dfrac{31}{3}\\\\\text{Finally:}\\\\y=-\dfrac{8}{5}x+\dfrac{31}{5}[/tex]
The length of a rectangle frame is represented by the expression 2x +8, and the width of the rectangle frame is represented by the expression 2x +6 what is the width of the rectangle frame that has a total area of 160 Square inches
Final answer:
The width of the rectangle frame with a total area of 160 square inches, and expressions for length (2x + 8) and width (2x + 6), is found to be 10 inches.
Explanation:
To solve for the width of the rectangle frame with an area of 160 square inches, where the length is represented by 2x + 8 and the width by 2x + 6, we need to set up an equation using the formula for the area of a rectangle, which is length × width. With the given area of 160 square inches, the equation is:
(2x + 8)(2x + 6) = 160
Let's expand this and solve for x:
4x² + 12x + 16x + 48 = 160
4x² + 28x + 48 = 160
4x² + 28x - 112 = 0
Divide everything by 4 to simplify:
x²+ 7x - 28 = 0
Factor this quadratic equation:
(x + 14)(x - 2) = 0
x = -14 or x = 2
Since a width cannot be negative, x = 2
Now, to find the width, replace x in the width expression:
Width = 2x + 6
Width = 2(2) + 6 = 4 + 6 = 10 inches
Thus, the width of the rectangle frame is 10 inches.
Global online music sales have exploded. It was expected that music lovers would spend 2 billion for online music in 2007, in scientific notation this number is?
Pls help ive been struggling on this for a while
Answer:
[tex]2*10^{9}[/tex]
Step-by-step explanation:
we know that
One billion is equal to one thousand million
1 billion is equal to 1,000,000,000
so
Multiply by 2
2 billion is equal to 2,000,000,000
Remember that
In scientific notation, a number is rewritten as a simple decimal multiplied by 10 raised to some power, n
n is simply the number of zeroes in the full written-out form of the number
In this problem n=9
so
[tex]2,000,000,000=2*10^{9}[/tex]
120 is increased by d % and increased by 25% . What is the result ?
Please see attached image for complete answer and steps in detail.
Answer:
The result is 150 + 1.5d
Step-by-step explanation:
We want to translate the wordings into algebraic expression.
Firstly, we increase 120 by d%
d% = d/100
So increasing 120 by d % means;
120 + (d/100 * 120)
= 120 + 1.2d
Then increase this by 25%
= (120 + 1.2d) + 25/100(120 + 1.2d)
= 120 + 1.2d + (120+1.2d)/4
= 120 + 1.2d + 30 + 0.3d
= 120 + 30 + 1.2d + 0.3d
= 150 + 1.5d
Which one of the following is equal to 1hector area? 10000m/square 10000m/square 100m/square
100000m/square
Answer:
10,000 m/square
Step-by-step explanation:
we know that
A hectare is a unit of area equal to [tex]10,000\ m^{2}[/tex]
The symbol is Ha
Verify each case
case 1) 10,000 m/square
The option is true
case 2) 100 m/square
The option is false
case 3) 100,000 m/square
The option is false
Find the equation of the axis of symmetry and the coordinates of the vertex of the graph of the function y = 2x2 + 4x –3.
Answer:
Equation of the parabola: [tex]y = 2x^{2} + 4x - 3[/tex].
Axis of symmetry: [tex]x= -1[/tex].
Coordinates of the vertex: [tex]\displaystyle \left(-1, -5\right)[/tex].
Step-by-step explanation:
The axis of symmetry and the coordinates of the vertex of a parabola can be read directly from its equation in vertex form.
[tex]y = a(x-h)^{2} +k[/tex].
The vertex of this parabola will be at [tex](h, k)[/tex]. The axis of symmetry will be [tex]x = h[/tex].
The equation in this question is in standard form. It will take some extra steps to find the vertex form of this equation before its vertex and axis of symmetry can be found. To find the vertex form, find its coefficients [tex]a[/tex], [tex]h[/tex], and[tex]k[/tex].
Expand the square in the vertex form using the binomial theorem.
[tex]y = a(x-h)^{2} +k[/tex].
[tex]y = a(x^{2} - 2hx + h^{2}) +k[/tex].
By the distributive property of multiplication,
[tex]y = (ax^{2} - 2ahx + ah^{2}) +k[/tex].
Collect the constant terms:
[tex]y = ax^{2} - 2ahx + (ah^{2} +k)[/tex].
The coefficients in front of powers of [tex]x[/tex] shall be the same in the two forms. For example, the coefficient of [tex]x^{2}[/tex] in the given equation is [tex]2[/tex]. The coefficient of [tex]x^{2}[/tex] in the equation [tex]y = ax^{2} - 2ahx + (ah^{2} +k)[/tex] is [tex]a[/tex]. The two coefficients need to be equal for the two equations to be equivalent. As a result, [tex]a = 2[/tex].
Similarly, for the term [tex]x[/tex]:
[tex]-2ah = 4[/tex].
[tex]\displaystyle h = -\frac{2}{a} = -1[/tex].
So is the case for the constant term:
[tex]ah^{2} + k = -3[/tex].
[tex]k = -3 - ah^{2} = -5[/tex].
The vertex form of this parabola will thus be:
[tex]y = 2(x -(-1))^{2} + (-5)[/tex].
The vertex of this parabola is at [tex](-1, -5)[/tex].
The axis of symmetry of a parabola is a vertical line that goes through its vertex. For this parabola, the axis of symmetry is the line [tex]x = -1[/tex].
the sum of 1/5 and twice a number is equal to 4/5 subtracted from three times the number. find the number.
Answer:
1
Step-by-step explanation:
Your equation may be written as follows:
[tex]\frac{1}{5} +2n=3n-\frac{4}{5}[/tex]
Start by multiplying both sides by 5 to clear your fractions.
[tex]\frac{1}{5} +2n=3n-\frac{4}{5} \\1+10n=15n-4[/tex]
Next, subtract 10n from both sides.
[tex]1+10n=15n-4\\1=5n-4[/tex]
Add 4 to both sides.
[tex]1=5n-4\\5=5n[/tex]
Divide both sides by 5 to solve for n.
[tex]5=5n\\1=n[/tex]
Final answer:
By setting up an equation 1/5 + 2x = 3x - 4/5 and solving for x, we find that the number is 1.
Explanation:
The problem involves finding a number when given a relationship involving fractions and that number. The relationship is: the sum of 1/5 and twice a number is equal to 4/5 subtracted from three times the number. To find the number, we set up an equation and solve for the variable, which represents the number.
Let's denote the number as x. Our equation can be written as:
1/5 + 2x = 3x - 4/5
We bring all the x terms on one side and the constants on the other to solve for x:
2x - 3x = -4/5 - 1/5
-x = -1
x = 1
true or false
x=3 when 5*6\x=10
Classify the following triangle. Check all that apply.
Answer:
obtuse, isosceles
Step-by-step explanation:
We have two angles that have the same measure - that means two sides are equal length. That means the triangle is isosceles
We have one angle that is greater than 90 degrees - that tells us the triangle is obtuse
Convert -sqrt3 - i to polar form. PLEASE HELP. Photo has more information
Answer:
-√3 - i ⇒ (2 , 7/6 π)
Step-by-step explanation:
* Lets explain how to convert a point in Cartesian form to polar form
- Polar coordinates of a point is (r , θ).
- The origin is called the pole, and the x axis is called the polar axis,
because every angle is dependent on it.
- The angle measurement θ can be expressed in radians or degrees.
- To convert from Cartesian Coordinates (x , y) to Polar
Coordinates (r , θ)
1. r = √( x² + y² )
2. θ = tan^-1 (y/x)
* Lets solve the problem
∵ The point in the Cartesian form is z = -√3 - i, where -√3 is the real
part and -i is the imaginary part
∴ The x-coordinate of the point is -√3
∴ The y-coordinate of the point is -1
∵ Both the coordinates are negative
∴ The point lies on the 3rd quadrant
- To convert it to the polar form find r and Ф
∵ [tex]r=\sqrt{x^{2}+y^{2}}[/tex]
∵ x = -√3 and y = -1
∴ [tex]r=\sqrt{(-\sqrt{3}) ^{2}+(-1)^{2}}=\sqrt{3+1}=\sqrt{4}=2[/tex]
∵ Ф = [tex]tan^{-1}\frac{y}{x}[/tex]
∴ Ф = [tex]\frac{-1}{-\sqrt{3}}=\frac{1}{\sqrt{3}}[/tex]
- The acute angle π/6 has tan^-1 (1/√3)
∵ The point is in the third quadrant
∴ Ф = π + π/6 = 7/6 π
- Lets write it in the polar form
∴ -√3 - i ⇒ (2 , 7/6 π)
Answer:
2cis 7pi/6
Step-by-step explanation:
simplify -(x+5) + 3x completely
Answer:2x-5
Step-by-step explanation:-(x+5)+3x
-x-5+3x=(3x-x) -5
=2x-5
what’s the inverse function
Answer:
[tex]f^{-1}(x)=-2x+6[/tex].
Step-by-step explanation:
[tex]y=f(x)[/tex]
[tex]y=3-\frac{1}{2}x[/tex]
The biggest thing about finding the inverse is swapping x and y. The inverse comes from switching all the points on the graph of the original. So a point (x,y) on the original becomes (y,x) on the original's inverse.
Sway x and y in:
[tex]y=3-\frac{1}{2}x[/tex]
[tex]x=3-\frac{1}{2}y[/tex]
Now we want to remake y the subject (that is solve for y):
Subtract 3 on both sides:
[tex]x-3=-\frac{1}{2}y[/tex]
Multiply both sides by -2:
[tex]-2(x-3)=y[/tex]
We could leave as this or we could distribute:
[tex]-2x+6=y[/tex]
The inverse equations is [tex]y=-2x+6[/tex].
Now some people rename this [tex]f^{-1}[/tex] or just call it another name like [tex]g[/tex].
[tex]f^{-1}(x)=-2x+6[/tex].
Let's verify this is the inverse.
If they are inverses then you will have that:
[tex]f(f^{-1}(x))=x \text{ and } f^{-1}(f(x))=x[/tex]
Let's try the first:
[tex]f(f^{-1}(x))[/tex]
[tex]f(-2x+6)[/tex] (Replace inverse f with -2x+6 since we had [tex]f^{-1})(x)=-2x+6[/tex]
[tex]3-\frac{1}{2}(-2x+6)[/tex] (Replace old output, x, in f with new input, -2x+6)
[tex]3+x-3[/tex] (I distributed)
[tex]x[/tex]
Bingo!
Let's try the other way.
[tex]f^{-1}(f(x))[/tex]
[tex]f^{-1}(3-\frac{1}{2}x)[/tex] (Replace f(x) with 3-(1/2)x since [tex]f(x)=3-\frac{1}{2}x[/tex])
[tex]-2(3-\frac{1}{2}x)+6[/tex] (Replace old input, x, in -2x+6 with 3-(1/2)x since [tex]f(x)=3-\frac{1}{2}x[/tex])
[tex]-6+x+6[/tex] (I distributed)
[tex]x[/tex]
So both ways we got x.
We have confirmed what we found is the inverse of the original function.
Answer:
[tex]\laege\boxed{f^{-1}(x)=-2x+6}[/tex]
Step-by-step explanation:
[tex]f(x)=3-\dfrac{1}{2}x\to y=3-\dfrac{1}{2}x\\\\\text{Exchange x to y and vice versa:}\\\\x=3-\dfrac{1}{2}y\\\\\text{Solve for}\ y:\\\\3-\dfrac{1}{2}y=x\qquad\text{subtract 3 from both sides}\\\\-\dfrac{1}{2}y=x-3\qquad\text{multiply both sides by (-2)}\\\\\left(-2\!\!\!\!\diagup^1\right)\cdot\left(-\dfrac{1}{2\!\!\!\!\diagup_1}y\right)=-2x-3(-2)\\\\y=-2x+6[/tex]
Determine whether the relation represents y as a function of x.
i need help with question 2. i think my answer is incorrect.
Answer:
395
You are 100% right! You go!
Step-by-step explanation:
We are given f(x)=5x^2-2x+8 and are asked to find the value of the function at x=9.
So replace x with (9):
f(9)=5(9)^2-2(9)+8
f(9)=5(81)-18+8 I did the exponent 9^2 and 2(9) in this step:
f(9)=405-18+8 I did 5(81) in this step
f(9)=405-10 I did -18+8 in this step
f(9)=395
simplify (2x^4y^3) x (6x^3y^2)
Answer:
[tex]\large\boxed{(2x^4y^3)(6x^3y^2)=6x^7y^5}[/tex]
Step-by-step explanation:
[tex](2x^4y^3)(6x^3y^2)\\\\=(2)(3)(x^4x^3)(y^3y^2)\qquad\text{use}\ a^na^m=a^{n+m}\\\\=6x^{4+3}y^{3+2}\\\\=6x^7y^5[/tex]
Linda is twice the age of Vera.
Tanya is four less than four times the age of Linda.
Their total age is two more than nine times the age of Vera.
How old is Tanya?
Answer:
Tanya is 20 years old
Step-by-step explanation:
Let the age of Vera = x years
The age of Linda is twice the age of Vera = 2x years
Tanya is four less than four times the age of Linda = 4(2x)-4 = 8x-4
Total age of Vera, Linda and Tanya is:
x+2x+8x-4
Combine the like terms:
11x-4
But now their total age is two more than nine times the age of Vera:
11x-4 = 9x+2
Solve the expression
Combine the like terms:
11x-9x=2+4
2x=6
Divide both the sides by 2
2x/2 = 6/2
x= 3
Thus the age of Vera is 3 years.
The age of Linda is 2x= 2*3 = 6 years
The age of Tanya is 8x-4 = 8*3 - 4 = 24-4 = 20years....
Write the slope-intercept form of the equation that passes through the point (4,-6) and is parallel to the line y = -3/4x - 5 y = -3/4x - 3 y = -3/4x + 3 y = 4/3x + 2/3 y = 4/3x - 34/3
Answer:
[tex]\large\boxed{y=-\dfrac{3}{4}x-3}[/tex]
Step-by-step explanation:
The slope-intercept form of an equation of a line:
y = mx + b
m - slope
b - y-intercept
Parallel lines have the same slope.
===========================================
We have the equation of the line: [tex]y=-\dfrac{3}{4}x-5[/tex]
The slope is [tex]m=-\dfrac{3}{4}[/tex].
Put the value of the slope and the coordinates of the point (4, -6) to an equation of a line:
[tex]-6=-\dfrac{3}{4}(4)+b[/tex]
[tex]-6=-3+b[/tex] add 3 to both sides
[tex]-3=b\to b=-3[/tex]
Finally:
[tex]y=-\dfrac{3}{4}x-3[/tex]
If f(x) = 4 – x2 and g(x) = 6x, which expression is equivalent to (9 - 1)(3)?
Answer:
(g − f) ( 3 ) = 23
Step-by-step explanation:
( g − f ) ( x ) = g ( x ) − f ( x )
= 6 x − ( 4 − x 2 )
= x 2 + 6 x − 4
to evaluate ( g - f ) ( 3 ) substitute x = 3 into ( g − f ) ( x )
( g − f ) = ( 3 ) 2 + ( 6 x 3 ) - 4 =23
For this case we have the following functions:
[tex]f (x) = 4-x ^ 2\\g (x) = 6x[/tex]
By definition we have to:
[tex](f-g) (x) = f (x) -g (x)\\(g-f) (x) = g (x) -f (x)[/tex]
Then, we find [tex](f-g) (x):[/tex]
[tex]f (x) -g (x) = 4-x ^ 2-6x = -x ^ 2-6x 4[/tex]
We evaluate the function in 3:
[tex](f-g) (3) = - (3) ^ 2-6 (3) 4 = -9-18 4 = -27 4 = -23[/tex]
Now we find[tex](g-f) (x):[/tex]
[tex]g (x) -f (x) = 6x- (4-x ^ 2) = 6x-4 x ^ 2 = x ^ 2 6x-4[/tex]
We evaluate the function in 3
[tex](g-f) (3) = 3 ^ 2 6 (3) -4 = 9 18-4 = 23[/tex]
Answer:
[tex](f-g) (3) = - 23\\(g-f) (3) = 23[/tex]
What is each power of i with its multiplicative inverse.
1. i
2. i ^2
3. i ^3
4. i ^4
Answer:
1) multiplicative inverse of i = -i
2) Multiplicative inverse of i^2 = -1
3) Multiplicative inverse of i^3 = i
4) Multiplicative inverse of i^4 = 1
Step-by-step explanation:
We have to find multiplicative inverse of each of the following.
1) i
The multiplicative inverse is 1/i
if i is in the denominator we find their conjugate
[tex]=1/i * i/i\\=i/i^2\\=We\,\, know\,\, that\,\, i^2 = -1\\=i/(-1)\\= -i[/tex]
So, multiplicative inverse of i = -i
2) i^2
The multiplicative inverse is 1/i^2
We know that i^2 = -1
1/-1 = -1
so, Multiplicative inverse of i^2 = -1
3) i^3
The multiplicative inverse is 1/i^3
We know that i^2 = -1
and i^3 = i.i^2
[tex]1/i^3\\=1/i.i^2 \\=1/i(-1)\\=-1/i * i/i\\=-i/i^2\\= -i/-1\\= i[/tex]
so, Multiplicative inverse of i^3 = i
4) i^4
The multiplicative inverse is 1/i^4
We know that i^2 = -1
and i^4 = i^2.i^2
[tex]=1/i^2.i^2\\=1/(-1)(-1)\\=1/1\\=1[/tex]
so, Multiplicative inverse of i^4 = 1
which value is equivalent to (7x5x2/7x3)^2 x (5^0/2^-3)^3 x2^-9?
Answer:
100/9
Step-by-step explanation:
(7*5*2/7*3)² * (5^0/2^-3)³ * 2^-9
Solution:
We know that any number with power 0 = 1
(7*5*2/7*3)² * (1/2^-3)³ * 2^-9
Now cancel out 2 by 2
= (7*5*2/7*3)² * (1/1^-3)³ * 1^-9
=(70/21)² * (1)³/(1^-3)³ * 1^-9
=(10/3)^2 * 1/1^-1 * 1/1^9
=100/9 *1 *1
=100/9....
hat is the approximate area of the circle shown below?
A. 60 in 2
B. 119 in 2
c. 4536 in 2
d. 1134 in 2
Help Me Please!!!!!!!!!!!!!!!!!!!!!!
Answer:
d. 1134 inches squared
Step-by-step explanation:
The formula for the area of a circle is [tex]\pi r^2[/tex]
where r is the radius.
You are given r=19 here so replace r in [tex]\pi r^2[/tex] with 19 giving us:
[tex]\pi (19)^2[/tex]
Then it is to the calculator we go:
1134 inches squared